Linking the built environment with social capital: a case study of Mahabang Parang Settlement, Angono, Rizal - Peralta, Sheena Criselle R. (College of Architecture, University of the Philippines Diliman, 2025)
This study examined the relationship between the built environment and the formation of social capital within informal settlements, using Mahabang Parang settlement in Angono, Rizal, Philippines as a case study. The author investigated how specific architectural and environmental attributes influence bonding (familial and neighborly), bridging (inter-group), and linking (institutional connections) social capital, drawing on the theoretical frameworks of Bourdieu, Coleman, and Putnam. Employing a Person-Environment Fit (PE-fit) framework, the author analyzed the interplay between perceived socio-spatial contexts and objective environmental factors through survey-interviews of 229 residents of three puroks of the settlement, site observation and documentation. The findings reveal distinct manifestations of social capital across these levels and types of relations between the social and spatial context at the three levels. The proximity of houses, perceived safety of streets and house design have an impact on residents' bonding social capital. Purok proximity or walkability, permeability and boundaries have an impact on inter-purok relations or the residents' bridging social capital. The connectivity of the settlement and fixed communal spaces have a relation with the community's linking social capital with the government and other institutions. Lastly, mobilization of the social capital of the community could be used to promote sustainable development within the settlement. This research contributes to a contextual understanding of socio-spatial dynamics in informal settlements, offering a flexible framework for analyzing the built environment's role in cultivating social capital. The findings and recommendations are pertinent for government and non-government institutions, designers, and researchers engaged in promoting person-centric and social-centric sustainable approaches to informal settlement upgrading.